2019
DOI: 10.1080/1828051x.2019.1686433
|View full text |Cite
|
Sign up to set email alerts
|

In vitro rumen fermentation characteristics of substrate mixtures with soybean meal partially replaced by microbially fermented yellow wine lees

Abstract: This study was conducted to evaluate the effects of replacing soybean meal (SBM) with unfermented and microbially fermented yellow wine lees (YWL) mix on the in vitro rumen fermentation characteristics of substrate mixtures. Both types consisting of YWL at 400 g/kg were included in the mixtures at different ratios (1:0, 1:1, 1:2, 1:5 and 0:1, w/w) to replace SBM. Microbial fermentation of YWL did not have a negative impact on gas value (p> .05), increased microbial protein (MCP, p < .01) and in vitro crude pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…These model-derived parameters have been used in conjunction with information regarding substrate degradability and digesta passage rate to calculate extent of substrate degradation in the rumen [3][4][5][6]34]. This method has been successfully applied to typical monophasic sigmoidal and diminishing returns gas profiles to evaluate substrates based upon the extent of their degradability [3,5,6,[8][9][10][11][12][13][14]34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These model-derived parameters have been used in conjunction with information regarding substrate degradability and digesta passage rate to calculate extent of substrate degradation in the rumen [3][4][5][6]34]. This method has been successfully applied to typical monophasic sigmoidal and diminishing returns gas profiles to evaluate substrates based upon the extent of their degradability [3,5,6,[8][9][10][11][12][13][14]34].…”
Section: Discussionmentioning
confidence: 99%
“…where w 1 and w 2 are the relative weights assigned to the respective phases. If the profile resolves into a diminishing returns and a linear (with abrupt cut-off) component as in Equation 4, then Equations (5) and (8) respectively can be applied to the two phases and the overall extent calculated again using Equation (9). As an arbitrary rule of thumb, the asymptotic gas production values for the two phases (abrupt cut-off value if a phase is linear), viz.…”
Section: Extent Of Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Details, including cost of the experimental rations, are described in Supplementary Table S1. The percentage for YWL feed inclusion was based on the former in vitro study [20] and the DMI and milk yield of FM was similar to the control diet, reported in the previous production study [21]. All of the diets were isonitrogenous and isocaloric, with a forage-to-concentrate ratio of 60:40 (DM basis), and met the requirement of net energy for lactation (NE L ) producing 29 kg/day milk in dairy cows (Ministry of Agriculture of China, (Beijing, China), 2004) [21].…”
Section: Animal Experimental Designmentioning
confidence: 99%
“…We previously found that the antioxidant activity of the YWL can be improved when fermented with Candida utilis and Bacillus subtilis [ 19 ]. In our preliminary in vitro study, when the ratio of soybean meal (SBM) to unfermented (UM) or fermented YWL mix (FM) in the simulated ration was at 1:1 (DM basis), the gas production parameters and volatile fatty acids were optimized and functioned similarly to the rations with SBM as the main protein resource [ 20 ]. Moreover, we observed that total mixed rations (TMR) with partial replacement of SBM with UM/FM did not affect feed efficiency and milk compositions, indicating YWL as a potential protein source in dairy rations [ 21 ].…”
Section: Introductionmentioning
confidence: 99%